Accurate and sensitive total genomic DNA methylation analysis from sub-nanogram input with embedded SERS nanotags. Issue 17 (4th February 2016) - Wang, Yuling; Wee, Eugene J. H.; Trau, Matt
Abstract : Accurate and sensitive total genomic DNA methylation analysis from sub-nanogram input was demonstrated by using embedded SERS nanotags. Abstract : Sensitive and accurate total genomic DNA methylation analysis was demonstrated by surface-enhanced Raman scattering (SERS) via embedded internal SERS nanotags. The assay was sensitive to 0.2 ng input DNA while differentiating as low as 6.25% changes in DNA methylation. The method could also successfully differentiate cells before and after de-methylating drug-treatment and between tumor and normal biopsies.